S3_3 The Shadow of Balerion the Dread - Kamran, Aneesah; Doherty, Lauren; Rhodes, Kira (Physics Special Topics, 2017)
We investigated a legend within Game of Thrones which suggested that there was a dragon large enough to cast a shadow over entire towns as it flew overhead. For casting a shadow over Leicester, we would need a wingspan of 29.66km. For Manchester, the wingspan would be approximately 37.24km. For Birmingham, the wingspan would be 56.71km and for London, the wingspan would need to be 137.3km.